Crisis of the clinical method - Miguel Moreno Rodríguez (Medisur, 2010)
This is an opinion paper. The author identifies an universal crisis of the clinical method, with dangerous consequences in the practice of medicine. Among its main causes, there are discussed: a deterioration in the doctor-patient relationship, the undervaluation of clinics, the overvaluation of technology, and the indifference for general medicine. A call for attention is made for the restoration of clinical method values and to permanent seed its principles in all medical students and young doctors.